ANALISIS PENGARUH VARIASI SUHU DAN BAHAN BAKU KARBON AKTIF PADA SISTEM INSTALASI AIR BERSIH - Radjiq, Ahmad; Gunawan, Indra (MACHINERY Jurnal Teknologi Terapan, 2025)
This research analyzes the effect of temperature variations and activated carbon raw materials on clean water installation systems using brackish water as raw material. Water is a vital basic need, but the availability of clean water is still a problem in many areas. To overcome this, this research carried out a filtering process to process brackish water into clean water. Variations in temperature and types of active carbon raw materials, namely coconut shells and coal, were tested to determine the most optimal conditions in the filtering process. The research results showed that the quality of brackish water before and after the filtering process experienced significant changes. The effect of variations in temperature and type of raw material on the performance of activated carbon in filtering brackish water was tested using physical parameters (turbidity, taste, color, TDS) and chemical parameters (pH, Fe metal content). This research succeeded in finding the right temperature and active carbon raw materials to produce quality clean water, providing benefits to local communities by increasing the availability of clean water that is safe and suitable for consumption. The benefit of this research is that it provides practical solutions for processing brackish water into clean water and increases awareness of the importance of maintaining water quality for health. It is hoped that this research can become a reference for further research and implementation of similar technology in other areas that face similar problems. Keywords : Temperature, Activated Carbon, Water, Installation